The economist, 1843-1943 a centenary volume. - The Economist (London). ([London] Oxford University Press, 1943)
Weekly (except for combined issue the last week in Dec. and the first week in Jan.), Dec. 26, 1981- Weekly, Sept. 2, 1843-